Antiskid ceramic tile and preparation method thereof

Through the three-layer structure design and raw material ratio optimization, the anti-slip performance and wear resistance of anti-slip tiles are improved, and the problem of poor anti-slip effect in the existing technology is solved, especially the performance improvement under wet conditions, achieving efficient Anti-slip effect and environmentally friendly production process.

CN119263772AActive Publication Date: 2025-01-07GUANGDONG YUBANG CERAMICS CO LTD

Patent Information

Application Number
CN202411417416.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-07
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

It is difficult to effectively improve anti-slip performance while maintaining its aesthetics. Especially in wet conditions, the static friction coefficient is low, resulting in poor anti-slip effect. The raw material ratio lacks targeted optimization during the preparation process, which affects the yield and quality.

Method used

The anti-slip tiles with three-layer structure are designed, including a blank layer, an anti-slip layer and an anti-slip layer. By optimizing the raw material ratio and preparation process, the blank is constructed using lime, limestone powder, tiles clay, river sand, lithium porcelain stone and other materials. , quartz stone powder, potassium feldspar, alumina, silicon carbide and other materials form an anti-slip layer, and polished brick waste slag is used in the anti-slip layer, combined with sandblasting or embossing process to form an anti-slip texture to improve the friction coefficient.

Benefits of technology

显著增强了瓷砖的防滑性能,尤其在潮湿环境下,提高了摩擦系数和耐磨性,延长了使用寿命,并实现了废弃物的再利用,降低了生产成本和环境污染。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263772A_ABST
    Figure CN119263772A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of tiles, in particular to an antiskid tile and a preparation method thereof. The anti-slip ceramic tile comprises a green body layer, an anti-slip layer and an anti-slip layer which are sequentially stacked, the green body layer is composed of lime, limestone powder, ceramic tile cement and the like; the anti-skid layer is composed of quartz stone powder, potassium feldspar, aluminum oxide and the like; the preparation method comprises the following steps: preparing the green body layer, preparing glaze slip of the anti-slip layer and the anti-slip layer, glazing and firing. By designing the three-layer structure and optimizing the raw material ratio and the preparation process, the ceramic tile plaster, the river sand or yellow sand, the lithium chinastone and other raw materials are used for forming a basic framework and performance of a ceramic tile green body, and the suspending aid, the bentonite and the sodium silicate are used for improving the dispersity, the cohesiveness and the fluidity of the raw materials; the material of the anti-skid layer has good wear resistance, hardness and anti-skid performance; the anti-slip layer material can form a stable compound in the glaze layer, and the anti-slip performance and attractiveness of the ceramic tile can be enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic tiles, and in particular to an anti-slip ceramic tile and a preparation method thereof. Background Art

[0002] The design principle of anti-slip tiles is mainly based on the principles of mechanical bite and vacuum adsorption in physics. By forming a macro or micro uneven structure on the surface of the tile, when the sole contacts the tile surface and applies pressure, this structure can produce a mechanical bite with the sole, and at the same time use the vacuum adsorption effect to enhance the friction between the tile and the sole, thereby achieving an anti-slip effect.

[0003] The existing anti-slip ceramic tiles have a single structural design and adopt a simple single-layer or double-layer structure, which makes it difficult to effectively improve the anti-slip performance while maintaining aesthetics. At the same time, in the preparation process of existing ceramic tiles, the ratio of raw materials often lacks targeted optimization, resulting in the basic skeleton and performance of the ceramic tile body being less than ideal, and the dispersion, adhesion and fluidity of the raw materials being poor, affecting the yield and quality of the product; in addition, due to deficiencies in raw material selection and structural design, existing ceramic tiles are often difficult to meet high standards in terms of anti-slip performance, especially under wet conditions, the static friction coefficient of the ceramic tiles is low, resulting in poor anti-slip effect. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide an anti-slip tile and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: An anti-skid tile comprises a body layer, an anti-skid layer and a non-slip layer which are stacked in sequence; The green body layer is composed of the following raw materials in parts by weight: 15-25 parts of lime, 5-10 parts of limestone powder, 18-22 parts of tile adhesive, 18-20 parts of river sand or yellow sand, 8-12 parts of lithium porcelain stone, 2.1-3.5 parts of suspending agent, 1-2 parts of bentonite and 0.9-1.5 parts of sodium silicate; The anti-slip layer is composed of the following raw materials in parts by weight: 20-25 parts of quartz powder, 12-16 parts of potassium feldspar, 6-8 parts of aluminum oxide, 5-7 parts of silicon carbide and 2-4 parts of magnesium oxide; The anti-slip layer is composed of the following raw materials in parts by weight: 10-15 parts of polished tile waste residue, 2-4 parts of aluminum oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide and 0.5-1 part of iron oxide.

[0006] Preferably, the polishing brick waste residue is the waste powder ground off when polishing the polishing brick, which is obtained by crushing, grinding, and then screening through a sieve.

[0007] Preferably, the anti-slip layer also includes 0.1-0.5 parts of glass powder to increase the glossiness and wear resistance of the glaze.

[0008] A method for preparing anti-slip tiles comprises the following steps: Step (1) Preparation of green body layer: Mix lime, limestone powder, tile adhesive, river sand or yellow sand, lithium porcelain stone, suspending agent, bentonite and sodium silicate in a formula ratio, grind them by a ball mill, sieve to obtain a uniform green body powder, use a mold to press the green body powder to obtain a green body layer green body, dry it to a moisture content of 0.2-0.4% and set it aside; Step (2) Preparation of anti-skid layer and anti-skid layer glaze slurry: Quartz powder, potassium feldspar, aluminum oxide, silicon carbide and magnesium oxide are mixed according to the formula ratio, finely ground by a ball mill, and the ingredients are evenly mixed, and sieved to remove impurities to prepare an anti-slip layer glaze slurry with a specific gravity of 1.5-1.8g / mL; Polishing tile waste residue, aluminum oxide, sodium oxide, zinc oxide and iron oxide are mixed according to the formula ratio, finely ground by a ball mill, and the components are evenly mixed, and sieved to remove impurities to prepare a non-slip layer glaze slurry with a specific gravity of 1.4-1.9g / mL; Step (3) Glazing and firing: Spray or print a layer of anti-slip glaze slurry evenly on the surface of the dried body layer, with a glaze amount of 200-250g / m 2 After the anti-skid layer of the blank is dry, spray or print the anti-skid glaze slurry evenly on the surface of the anti-skid layer. The glaze amount is 150-200g / m 2 , forming a ceramic tile body; The glazed ceramic tile body is sent into the kiln for firing so that the glaze layer and the body layer are closely combined. After the firing is completed, it is cooled, edged and graded to obtain the finished anti-slip ceramic tile.

[0009] Preferably, in step (2) of preparing the anti-skid layer and the anti-slip layer glaze slurry, it also includes adding 0.1-0.3 parts of an anti-settling agent to the anti-skid layer glaze slurry to prevent the glaze slurry from stratifying during storage and use.

[0010] Preferably, during the glazing and firing step (3), a sandblasting or embossing process is used to form an anti-slip texture on the surface of the anti-slip layer glaze slurry to improve the anti-slip effect.

[0011] Preferably, during the glazing and firing step (3), the temperature in the kiln is controlled to be 1150-1250° C. and maintained for 30 min-2 h to ensure that the glaze layer and the body layer are fully bonded.

[0012] Preferably, after the glazing and firing in step (3) are completed, the surface of the anti-slip ceramic tile is polished to improve its surface smoothness and aesthetics.

[0013] Preferably, the glaze amount of the anti-slip layer glaze is 200-250g / m 2 .

[0014] Preferably, the glaze amount of the anti-slip layer glaze slurry is 150-200g / m 2 .

[0015] The beneficial effects achieved by the present invention are as follows: 1. The present invention can enhance the anti-skid performance of ceramic tiles by designing a three-layer structure and optimizing the raw material ratio and preparation process. Ceramic tile adhesive, river sand or yellow sand, lithium porcelain stone and other raw materials are used to form the basic skeleton and performance of the ceramic tile body. Suspending agents, bentonite and sodium silicate improve the dispersibility, adhesion and fluidity of the raw materials, ensuring that the ceramic tile body has good process performance during the molding process; lime is used in the ceramic tile body to adjust the chemical composition, enhance adhesion and improve physical properties, and limestone powder is used as a filler or reinforcing agent; the anti-skid layer is composed of raw materials such as quartz powder, potassium feldspar, aluminum oxide, silicon carbide and magnesium oxide, and these materials have good wear resistance, hardness and anti-skid performance; the anti-skid layer is composed of raw materials such as polished tile waste, aluminum oxide, sodium oxide, zinc oxide and iron oxide, and these materials can form stable compounds in the glaze layer to improve the anti-skid performance and aesthetics of the ceramic tile.

[0016] 2. The present invention introduces high-efficiency anti-slip materials such as silicon carbide into the anti-slip layer, and combines sandblasting or embossing technology to form an anti-slip texture on the glaze surface, thereby effectively increasing the friction coefficient of the tile surface, so that it can have a good anti-slip effect even in a humid environment.

[0017] 3. The present invention can enhance the glossiness of the glaze surface, improve the wear resistance of the tile and extend its service life by adding glass powder to the anti-slip layer.

[0018] 4. The present invention uses polished brick waste as the main raw material of the anti-slip layer, which not only reduces production costs, but also realizes waste recycling, reduces environmental pollution and waste of resources.

[0019] 5. The present invention ensures the stability and consistency of the quality of the tile by controlling the raw material ratio, glaze amount and firing temperature and other parameters in the preparation process, and ensures the close combination of the glaze layer and the body layer, which helps to improve the overall performance of the anti-slip tile. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a schematic flow chart of the method for preparing the anti-slip ceramic tiles. DETAILED DESCRIPTION

[0021] The present invention provides an anti-slip tile and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The invention provides an anti-skid tile, comprising a body layer, an anti-skid layer and an anti-slip layer which are stacked in sequence; the body layer is composed of the following raw materials in parts by weight: 15-25 parts of lime, 5-10 parts of limestone powder, 18-22 parts of tile adhesive, 18-20 parts of river sand or yellow sand, 8-12 parts of lithium porcelain stone, 2.1-3.5 parts of suspending agent, 1-2 parts of bentonite and 0.9-1.5 parts of sodium silicate; The anti-slip layer is composed of the following raw materials in parts by weight: 20-25 parts of quartz powder, 12-16 parts of potassium feldspar, 6-8 parts of aluminum oxide, 5-7 parts of silicon carbide and 2-4 parts of magnesium oxide; The anti-slip layer is composed of the following raw materials in parts by weight: 10-15 parts of polished tile waste residue, 2-4 parts of aluminum oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide and 0.5-1 part of iron oxide.

[0023] The polishing brick waste residue is waste powder ground off when polishing the polishing brick, which is obtained by crushing, grinding, and then screening through a sieve.

[0024] The anti-slip layer also includes 0.1-0.5 parts of glass powder to increase the glossiness and wear resistance of the glaze.

[0025] A method for preparing anti-slip tiles, such as Figure 1 As shown, the following steps are included: Step (1) Preparation of green body layer: Mix lime, limestone powder, tile adhesive, river sand or yellow sand, lithium porcelain stone, suspending agent, bentonite and sodium silicate in a formula ratio, grind them by a ball mill, sieve to obtain a uniform green body powder, use a mold to press the green body powder to obtain a green body layer green body, dry it to a moisture content of 0.2-0.4% and set it aside; Step (2) Preparation of anti-skid layer and anti-skid layer glaze slurry: Quartz powder, potassium feldspar, aluminum oxide, silicon carbide and magnesium oxide are mixed according to the formula ratio, finely ground by a ball mill, the components are evenly mixed, and sieved to remove impurities to prepare an anti-skid layer glaze slurry with a specific gravity of 1.5-1.8g / mL. 0.1-0.3 parts of an anti-settling agent are added to the anti-skid layer glaze slurry as needed to prevent the glaze slurry from stratification during storage and use; Polishing tile waste residue, aluminum oxide, sodium oxide, zinc oxide and iron oxide are mixed according to the formula ratio, finely ground by a ball mill, and the components are evenly mixed, and sieved to remove impurities to prepare a non-slip layer glaze slurry with a specific gravity of 1.4-1.9g / mL; Step (3) Glazing and firing: Spray or print a layer of anti-slip glaze slurry evenly on the surface of the dried body layer, with a glaze amount of 200-250g / m 2 , use sandblasting or embossing technology to form anti-skid texture on the surface of the anti-skid layer glaze slurry to improve the anti-skid effect. After the anti-skid layer surface of the blank is dry, spray or print the anti-skid layer glaze slurry evenly on the surface of the anti-skid layer. The glaze amount is 150-200g / m 2 , forming a ceramic tile body; The glazed ceramic tile body is sent into the kiln for firing. The temperature in the kiln is controlled at 1150-1250℃ and maintained for 30min-2h to make the glaze layer and the body layer closely bonded. After firing, it is cooled, edged and graded to obtain the finished anti-slip ceramic tile, and the surface of the anti-slip ceramic tile is polished.

[0026] Embodiment 1: A non-slip tile, the preparation method of which comprises the following steps: Step (1) Preparation of green body layer: 20 parts of lime, 8 parts of limestone powder, 20 parts of tile glue, 19 parts of river sand, 10 parts of lithium porcelain stone, 2.8 parts of suspending agent, 1.5 parts of bentonite and 1.2 parts of sodium silicate are mixed evenly, finely ground by a ball mill, sieved to obtain a uniform green body powder, and the green body powder is pressed into shape by a mold to obtain a green body layer green body, which is dried to a moisture content of 0.3% and then used for later use; Step (2) Preparation of anti-skid layer and anti-skid layer glaze slurry: 23 parts of quartz powder, 14 parts of potassium feldspar, 7 parts of aluminum oxide, 6 parts of silicon carbide, 3 parts of magnesium oxide, and 0.3 parts of glass powder were mixed evenly, finely ground by a ball mill, and sieved to remove impurities to prepare an anti-skid layer glaze slurry with a specific gravity of 1.6 g / mL. 0.2 parts of an anti-settling agent were added to the anti-skid layer glaze slurry; 12 parts of polished tile waste, 3 parts of aluminum oxide, 1.5 parts of sodium oxide, 1.5 parts of zinc oxide and 0.8 parts of iron oxide were mixed evenly, finely ground by a ball mill, and sieved to remove impurities to prepare a non-slip layer glaze slurry with a specific gravity of 1.6 g / mL; Step (3) Glazing and firing: Spray a layer of anti-slip glaze slurry evenly on the surface of the dried body layer, with a glaze amount of 220g / m 2 Use sandblasting or embossing technology to form anti-slip texture on the surface of the anti-slip layer glaze slurry. After the anti-slip layer surface of the blank is dry, spray the anti-slip layer glaze slurry evenly on the surface of the anti-slip layer. The glaze amount is 170g / m 2 , forming a ceramic tile body; The glazed ceramic tile body is sent into the kiln for firing. The temperature in the kiln is controlled at 1200℃ and maintained for 1 hour to allow the glaze layer to be tightly combined with the body layer. After firing, it is cooled, edged and graded to obtain the finished anti-slip ceramic tile, and the surface of the anti-slip ceramic tile is polished.

[0027] Embodiment 2: A non-slip tile, the preparation method of which is different from that of Embodiment 1 in that: In the green body layer, lime is 15 parts, limestone powder is 10 parts, tile adhesive is 22 parts, river sand is 20 parts, lithium porcelain stone is 12 parts, suspending agent is 3.2 parts, bentonite is 2 parts, and sodium silicate is 1.5 parts; The anti-slip layer comprises 20 parts of quartz powder, 16 parts of potassium feldspar, 8 parts of aluminum oxide, 7 parts of silicon carbide and 4 parts of magnesium oxide; In the anti-slip layer, the polishing tile waste residue is 10 parts, the aluminum oxide is 4 parts, the sodium oxide is 2 parts, the zinc oxide is 2 parts and the iron oxide is 1 part.

[0028] Embodiment 3: A non-slip tile, the preparation method of which is different from that of Embodiment 1 in that: In the green body layer, lime is 25 parts, limestone powder is 6 parts, tile adhesive is 18 parts, yellow sand (replacing river sand) is 18 parts, lithium porcelain stone is 9 parts, suspending agent is 2.2 parts, bentonite is 1 part, and sodium silicate is 1 part; The anti-slip layer comprises 25 parts of quartz powder, 13 parts of potassium feldspar, 6 parts of aluminum oxide, 5 parts of silicon carbide and 2 parts of magnesium oxide; In the anti-slip layer, the polishing tile waste residue is 15 parts, the aluminum oxide is 2 parts, the sodium oxide is 1 part, the zinc oxide is 1 part and the iron oxide is 0.6 parts.

[0029] Comparative Example 1: A non-slip ceramic tile, the preparation method of which is different from that of Example 1 in that silicon carbide is not used in the non-slip layer.

[0030] Comparative Example 2: A non-slip ceramic tile, the preparation method of which is different from that of Example 1 in that: no non-slip glaze slurry is applied on the surface of the non-slip layer, that is, no non-slip glaze slurry is used.

[0031] Comparative Example 3: A non-slip tile, the preparation method of which is different from that of Example 1 in that no polishing tile waste residue is used in the non-slip layer.

[0032] Comparative Example 4: An anti-slip tile, the preparation method of which is different from that of Example 1 in that: no glass powder is used in the anti-slip layer.

[0033] Test Example: The anti-slip performance, wear resistance and glossiness of the anti-slip tiles prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were tested; 1. Anti-slip performance: The wet BPN and wet static friction coefficient of the "Pendulum Method" in the anti-slip performance test refer to "GB / T35153-2017"; the "Tilt Platform Method" refers to "EN16165:2021", and the test results are shown in Table 1; 2. Abrasion resistance: Tested in accordance with the national standard GB / T 3810.6-2016 Ceramic tile test method Part 6: Determination of abrasion resistance. The test results are shown in Table 1. 3. Glossiness: Tested in accordance with the national standard GB / T 9754-2007 Determination of 20°, 60° and 85° specular gloss of paints and varnishes without metallic pigments. The test results are shown in Table 1. Table 1 Test results of anti-skid performance, wear resistance and glossiness of anti-skid tiles of Examples and Comparative Examples

[0034] From the test results in Table 1, it can be seen that the anti-skid performance is measured by two indicators, namely, the wet BPN of the pendulum method and the wet static friction coefficient. The BPN values ​​of the embodiments are all above 45, which is much higher than that of the comparative example, and the wet static friction coefficient is also significantly higher than that of the comparative example, showing a stronger anti-skid ability; at the same time, in terms of the wear resistance loss (mg) indicator, the wear loss of the embodiments is relatively low, indicating that its surface wear resistance is excellent and can maintain the anti-skid effect for a long time; in terms of glossiness, the 20° angle glossiness value of the embodiments is at a relatively high level. In summary, the anti-skid ceramic tiles prepared in the embodiments of the present invention have excellent anti-skid performance and wear resistance, and also maintain good glossiness, which meets the market demand for high-end anti-skid ceramic tiles.

[0035] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A non-slip tile, characterized in that: It comprises a green body layer, an anti-skid layer and a non-slip layer stacked in sequence; the green body layer is composed of the following raw materials in parts by weight: 15-25 parts of lime, 5-10 parts of limestone powder, 18-22 parts of tile adhesive, 18-20 parts of river sand or yellow sand, 8-12 parts of lithium porcelain stone, 2.1-3.5 parts of suspending agent, 1-2 parts of bentonite and 0.9-1.5 parts of sodium silicate; The anti-slip layer is composed of the following raw materials in parts by weight: 20-25 parts of quartz powder, 12-16 parts of potassium feldspar, 6-8 parts of aluminum oxide, 5-7 parts of silicon carbide and 2-4 parts of magnesium oxide; The anti-slip layer is composed of the following raw materials in parts by weight: 10-15 parts of polished tile waste residue, 2-4 parts of aluminum oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide and 0.5-1 part of iron oxide.

2. The anti-slip tile according to claim 1, characterized in that: The polishing brick waste residue is waste powder ground off when polishing the polishing brick, which is obtained by crushing, grinding, and then screening through a sieve.

3. The anti-slip tile according to claim 1, characterized in that: The anti-slip layer also includes 0.1-0.5 parts of glass powder.

4. A method for preparing anti-slip tiles, characterized in that: The following steps are involved: Step (1) Preparation of green body layer: Mix lime, limestone powder, tile adhesive, river sand or yellow sand, lithium porcelain stone, suspending agent, bentonite and sodium silicate in a formula ratio, grind them by a ball mill, sieve to obtain a uniform green body powder, use a mold to press the green body powder to obtain a green body layer green body, dry it to a moisture content of 0.2-0.4% and set it aside; Step (2) Preparation of anti-skid layer and anti-skid layer glaze slurry: Quartz powder, potassium feldspar, aluminum oxide, silicon carbide and magnesium oxide are mixed according to the formula ratio, finely ground by a ball mill, and the ingredients are evenly mixed, and sieved to remove impurities to prepare an anti-slip layer glaze slurry with a specific gravity of 1.5-1.8g / mL; Polishing tile waste residue, aluminum oxide, sodium oxide, zinc oxide and iron oxide are mixed according to the formula ratio, finely ground by a ball mill, and the components are evenly mixed, and sieved to remove impurities to prepare a non-slip layer glaze slurry with a specific gravity of 1.4-1.9g / mL; Step (3) Glazing and firing: A layer of anti-skid glaze slurry is evenly sprayed or printed on the surface of the dried body layer, and after the anti-skid layer surface of the body is dried, an anti-skid glaze slurry is evenly sprayed or printed on the surface of the anti-skid layer to form a tile body; The glazed ceramic tile body is sent into the kiln for firing so that the glaze layer and the body layer are closely combined. After the firing is completed, it is cooled, edged and graded to obtain the finished anti-slip ceramic tile.

5. The method for preparing a non-slip tile according to claim 4, characterized in that: In step (2) of preparing the anti-skid layer and the anti-slip layer glaze slurry, the method further comprises adding 0.1-0.3 parts of an anti-settling agent to the anti-skid layer glaze slurry.

6. The method for preparing a non-slip tile according to claim 4, characterized in that: In step (3) of glazing and firing, a sandblasting or embossing process is used to form an anti-slip texture on the surface of the anti-slip layer glaze slurry.

7. The method for preparing a non-slip tile according to claim 4, characterized in that: In step (3) of glazing and firing, the temperature in the kiln is controlled at 1150-1250°C and maintained for 30 minutes to 2 hours.

8. The method for preparing anti-slip tiles according to claim 4, characterized in that: After the glazing and firing in step (3) are completed, the surface of the anti-slip tiles is polished.

9. The method for preparing anti-slip tiles according to claim 4, characterized in that: The glaze amount of the anti-slip layer glaze slurry is 200-250g / m 2 .

10. The method for preparing anti-slip tiles according to claim 4, characterized in that: The glaze amount of the anti-slip layer glaze slurry is 150-200g / m 2 .

Citation Information

Patent Citations

  • Bump texture glazed tile and preparation method thereof

    CN104311162A

  • Glazed tile waste residue recycling method

    CN106116501A

  • Anti-skid glaze and anti-skid floor tile

    CN108706874A

  • Anti-caking ceramic tile adhesive and preparation method thereof

    CN110204277A

  • Super-wear-resistant antiskid ceramic tile and preparation method thereof

    CN111995437A

Cited By

  • Golden velvet texture easy-to-clean anti-skid ceramic tile and preparation process thereof

    CN121021198A